Innovative Pricing Strategies to Increase Profits - Marburger, Daniel (Business Expert Press, 2012)
Ebook from IG Library ; According to the economic theory of the firm, businesses strive to determine the single price that maximizes profits. In fact, many firms can extract more revenue and increase profits with pricing strategies that are far more innovative than the single-price strategy. However, in the world of pricing, there is no â€œone size fits allâ€ strategy.